Tourism and Erotic Imaginaries in Wartime Paris: French and Germans during the Occupation, 1940-1944 - Bertram M. Gordon (Via@)
This essay focuses on the intersections of tourism, war, and erotics in occupied Paris during the Second World War. Too frequently, tourism is considered a only peacetime phenomenon. War, however, can produce its own tourism, as was true of German soldiers in occupied Paris during the Second World War. A specially designated unit of the Wehrmacht arranged tours for thousands of its young soldiers, many of whom had never before left their native towns and villages. Their time in Paris, a city with an already established imaginary of sensuality, opened previously undreamed of possibilities for sexual adventures both imagined and real. Although erotic imaginaries can be difficult for the historian to trace, some idea of them is provided in the diaries of Ernst Jünger, a well-known German officer and writer, who while stationed in Paris toured the city and seems to have had at least a few sexual encounters with local women along the way. The many relationships between German soldiers and Frenchwomen produced tens of thousands of children born during the Occupation. Other soldiers consorted with streetwalkers or visited brothels, carefully regulated by the German authorities. Erotic behavior and imaginaries clearly reflected the power imbalances of the time.With the 1944 liberation of France, Allied soldiers replaced the Germans but the power imbalances remained and the erotic tourism continued. The Liberation also brought accusations against “horizontal collaborators,” or Frenchwomen accused of having had sexual relations with the Germans. Many of those accused were paraded with their heads shaven or worse in French town and cities, reflecting a sense of emasculation in postwar France. In these many ways, erotics was linked to tourism and war. This essay surveys some of the many expressions of erotic feeling in occupied Paris. Addressing the complex intersections of tourism, war, and erotics, it seeks to encourage further research in their linkages.